Fostering Inquiry: The Impact of Cross-Curricular Professional Development on STEM Teacher Practices - Mirna Mendoza Wilson; Faiza Zafar; Carolyn Nichol (Education Sciences)
This study investigated the impact of sustained, inquiry-based professional development (PD) on K-12 STEM educators’ instructional practices, with a particular focus on integrated mathematics and science teaching. As STEM education becomes increasingly vital in preparing students to address global challenges, educators face the challenge of adapting their teaching strategies to foster meaningful, engaging, and effective learning experiences. Inquiry-based learning (IBL) has emerged as a promising approach through its emphasis on student-driven exploration and collaborative learning. However, its effective implementation often requires targeted PD. This qualitative study examines the ConocoPhillips Applied Math Program (AMP!), a sustained teacher PD program focused on mathematics and science instruction, to investigate how it supported teachers’ shift toward inquiry-based practices. Semi-structured interviews with six past AMP! participants revealed that the program positively influenced teachers’ content knowledge, pedagogical strategies, and confidence, leading to better student engagement and achievement. This study also highlighted the importance of addressing the practical challenges of IBL implementation, such as teachers’ time constraints and resistance to adopting new pedagogical strategies. The findings emphasized the need for PD programs to prioritize adaptability and provide long-term support and content aligned with teachers’ immediate needs.